ADHD and Asperger syndrome in smart kids and adults : twelve stories of struggle, support, and treatment - Brown, Thomas E., 1942- (New York, NY : Routledge, 2022)
"ADHD and Asperger Syndrome in Smart Kids and Adults offers detailed examples of individuals who have above average cognitive intelligence, but struggle with executive function impairments of ADHD and significant social-emotional impairments of Asperger syndrome. The book centers around twelve case studies of bright children, teens, and adults treated for both ADHD and Asperger syndrome. Each chapter describes diverse examples of their strengths and their difficulties and explains how these individuals can be helped with appropriate treatment to overcome their ADHD impairments and to improve their ability to understand and interact more effectively with others. Case examples are followed by updated, science-based descriptions of these disorders. Providing science-based information about ADHD and Asperger syndrome in clearly understandable, accessible language, this text is ideal for clinicians, educators, social workers, medical and mental health service providers, and parents of those struggling with such impairments. It also argues for restoring the diagnosis of Asperger Syndrome to diagnostic manuals of the American Psychiatric Association and World Health Organization"--
Keywords: Asperger's syndrome in children; Attention-deficit-disordered children; Attention-deficit hyperactivity disorder; PSYCHOLOGY / Psychopathology / Attention-Deficit Disorder (ADD-ADHD)